PEMBERDAYAAN PELAKU EKONOMI DITINJAU DARI PERSEPSI DAN KEBUTUHAN PENINGKATAN KOMPETENSI AKUNTANSI (Studi Karyawan Pelaku Usaha Komputer dan Jaringan di Batam - firdaus hamta; hendra hendra (Universitas Riau Kepulauan, 2019)
ABSTRACTThis research is the empowerment of economic actors in terms of perceptions and needs in increasing the potential of accounting human resources for business people in computers and networks in Batam. The study was conducted with a descriptive qualitative method with 30 informants from accounting and financial employees in computer business and network operators in Batam. Research analysis techniques through data collection, frequency, data reduction, analysis and conclusions. The results of the study that economic actors, especially computer and network businesses in Batam, require an increase in knowledge on journal entries for transactions and the need for adequate accounting records in the process of preparing financial reports and accounting systems to improve internal control. Understanding of computer-based accounting information systems in managing financial statementsKeywords: Empowerment of Economic Activities Accounting Competencies